Mapping Solution for Programmable Intelligent Spaces Based on Computer Vision - Izabel, Vinícius Hernech; Menines, Mateus Sobrinho; Oliveira, Matheus Dutra de; Mello, Ricardo Carminati de; Vassallo, Raquel Frizera (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This paper presents a mapping approach to be applied in intelligent spaces based on computer vision. By using cameras installed in the environment, the three-dimensional pose of mobile robots can be recovered through visual odometry, that provides a global and more accurate localization without cumulative errors. This enables the creation of high-quality maps that better represent the environment, ensuring invariance concerning the robot's reference frame and effectively addressing the kidnapped robot problem without compromising the map's integrity. The result is a robust mapping system capable of supporting more complex navigation tasks.